Factors Affecting Student Views Of Afghanistan And Thailand About Islamic Education Curriculum Content In Pondok Pesantren Luhur Wahid Hasyim Semarang - Nur Setyaningrum (Pascasarjana IAIN Metro, 2018)
This paper describes the analysis of the factors that led to their different views and Thailand Afghan students at the University of Wahid Hasyim about the content of curriculum in Pondok Pesantren Luhur Wahid Hasyim (PPLWH) Semarang. The background of this work, first, the students of Afghanistan to counter the unwillingness and the opt-out on non-formal education in PPLWH. One reason for the problem because the curriculum content presented too dense. Second, on the other hand there is uniqueness, students demonstrated Thailand. Namely, the existence of conditions of Thai students learning environment that is unstable and a variety of issues as well as negative fact, it strengthens their reaction to learning through pesantren education offered at the University of Wahid Hasyim. The second view of the type of student on Indonesian pesantren curriculum content is very important, one of them in Pondok Wahid Hasyim. This is because the University of Wahid Hasyim is the University of Nahdlatul 'Ulama in Indonesia which implemented a system of boarding schools. The other reason for the two types of these students have different cultural backgrounds (the Middle East and Southeast Asia) but still in one ideology, Islam.